2006
DOI: 10.1111/j.1472-765x.2006.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella Typhimurium and Listeria monocytogenes using high-pressure treatments: destruction or sublethal stress?

Abstract: Aims:  To investigate potential resuscitation of Listeria monocytogenes and Salmonella Typhimurium after high hydrostatic pressure treatments. Methods and Results:  Pressure treatments were applied at room temperature for 10 min on bacterial suspensions in buffers at pH 7 and 5·6. Total bacterial inactivation (8 log10 CFU ml−1 of bacterial reduction) obtained by conventional plating was achieved regarding both micro‐organisms. Treatments at 400 MPa in pH 5·6 and 600 MPa in pH 7 for L. monocytogenes and at 350 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Data obtained using microscopy and flow cytometry (Ananta et al, 2004;Ritz et al, 2001Ritz et al, , 2006 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Data obtained using microscopy and flow cytometry (Ananta et al, 2004;Ritz et al, 2001Ritz et al, , 2006 …”
mentioning
confidence: 99%
“…Data obtained using microscopy and flow cytometry (Ananta et al, 2004;Ritz et al, 2001Ritz et al, , 2006 suggests that at pressure levels of approximately 400 MPa cell integrity is maintained, that only very limited cell destruction occurs and metabolic activity is largely retained for various Grampositive bacteria, including L. monocytogenes. It was concluded that although cell viability was lost, HPP-treated cells were sublethally injured and were potentially capable of recovery back to culturability (Ritz et al, 2006). Physiological studies have also demonstrated that increasing HPP pressure levels results in metabolic indicators (for example the activity of the LmrP membrane transporter) exhibiting an accelerated decline (Kilimann et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HHP results in a decrease in biomembrane fluidity brought about by phase transition, which can result in membrane rupture and in denaturation of the membrane-bound proteins causing a loss of functionality of these proteins (San Martin et al 2002). Additionally, HHP acts instantaneously and uniformly in a food product and its efficacy is independent of food composition, shape, size, as well as exerting a minimal adverse effect on food quality (Ritz et al 2006). The use of HHP systems for processing raw meat, fish, and shellfish has expanded, making it often the first choice for the preservation of heat-sensitive products.…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, different procedures are available to inactivate bacteria and fungi, including their spores, in human bone transplants (48). The most efficient methods of inactivation are gamma irradiation and thermal inactivation as well as chemical sterilization methods such as the peracetic acid-ethanol treatment of bone (49).…”
Section: Effect Of Hhp-treatment On Viability Of Microorganisms In Bonementioning
confidence: 99%